From the Structural and (Dys)Function of ATP Synthase to Deficiency in Age-Related Diseases - Caterina Garone; Andrea Pietra; Salvatore Nesci (Life, 2022)
The ATP synthase is a mitochondrial inner membrane complex whose function is essential for cell bioenergy, being responsible for the conversion of ADP into ATP and playing a role in mitochondrial cristae morphology organization. The enzyme is composed of 18 protein subunits, 16 nuclear DNA (nDNA) encoded and two mitochondrial DNA (mtDNA) encoded, organized in two domains, FO and F1. Pathogenetic variants in genes encoding structural subunits or assembly factors are responsible for fatal human diseases. Emerging evidence also underlines the role of ATP-synthase in neurodegenerative diseases as Parkinson’s, Alzheimer’s, and motor neuron diseases such as Amyotrophic Lateral Sclerosis. Post-translational modification, epigenetic modulation of ATP gene expression and protein level, and the mechanism of mitochondrial transition pore have been deemed responsible for neuronal cell death in vivo and in vitro models for neurodegenerative diseases. In this review, we will explore ATP synthase assembly and function in physiological and pathological conditions by referring to the recent cryo-EM studies and by exploring human disease models.